Paternalistic leadership and its impact in promoting positive psychological capital: An analytical exploratory study in private universities and colleges for the Holy Karbala Governorate - Hurajah Al Hasnawi, Hussein; Oudah Abed, Marwa (Iraqi Journal for Administrative Sciences, 2024)
The current research aims at an impact of Paternalistic leadership in positive psychosocial capital at a sample level of universities and civil. In order to reach results, an analytical descriptive approach and data collection were used through the questionnaire, the research community included six universities and civil colleges in the Holy Governorate of Karbala and the research sample (158) of staff. The study has reached a range of conclusions, most importantly, with the existence of a significant links and an impact among Paternalistic leadership and positive psychological capital The existence of an impact relationship of a significant indication of the sub-variable of independent Paternalistic leadership with positive psychological capital. Finally, the research concluded with a group of recommendations, most notably the need to invest a positive impact of Paternalistic leadership in positive psychological capital Through the fact that universities and colleges have developed proactive plans and deepen career awareness among leaders and staff to benefit from Paternalistic leadership practices in promoting positive psychological capital.